2016
DOI: 10.1111/josi.12181
|View full text |Cite
|
Sign up to set email alerts
|

Altering Perceived Cultural and Economic Threats can Increase Immigrant Helping

Abstract: We report two experimental studies in which we investigated the effects of perceived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
15
0
2
Order By: Relevance
“…Two studies demonstrated that whereas moral threats did not influence participants’ prosocial tendencies, the affirmation of Israeli Jews’ (Study 1) and Palestinians’ (Study 2) in‐group agency allowed their morality‐related needs and considerations to come to fore, leading to stronger mutual prosocial tendencies. The conclusion derived from these studies—that group members need to feel secure and agentic before their morality‐related needs can come to the fore—is consistent with the finding of Burhan and van Leeuwen () that the removal of perceived threat is a prerequisite for fostering support and hospitality toward immigrants among host society members. Our conclusion is also consistent with Leach et al.’s () argument that in its emphasis on power‐related needs in intergroup relations, traditional social psychological theorizing has overlooked the importance of morality.…”
Section: Discussionsupporting
confidence: 85%
“…Two studies demonstrated that whereas moral threats did not influence participants’ prosocial tendencies, the affirmation of Israeli Jews’ (Study 1) and Palestinians’ (Study 2) in‐group agency allowed their morality‐related needs and considerations to come to fore, leading to stronger mutual prosocial tendencies. The conclusion derived from these studies—that group members need to feel secure and agentic before their morality‐related needs can come to the fore—is consistent with the finding of Burhan and van Leeuwen () that the removal of perceived threat is a prerequisite for fostering support and hospitality toward immigrants among host society members. Our conclusion is also consistent with Leach et al.’s () argument that in its emphasis on power‐related needs in intergroup relations, traditional social psychological theorizing has overlooked the importance of morality.…”
Section: Discussionsupporting
confidence: 85%
“…Burhan and van Leeuwen () present two experiments that address the relationships between immigrants and members of the host society and center on the question of how altering perceived cultural and economic challenges can increase helping and hospitality toward immigrants. Results from the first study showed that people who perceived immigrants as less of a threat to the society's economy were more willing to provide immigrants with empowerment help and less likely to expect immigrants to solve their own problems.…”
Section: The Current Journal Of Social Issues Volumementioning
confidence: 99%
“…When a group of immigrants is seen as economically or culturally threatening, they are less likely to receive support from their new country compared to those who are seen as nonthreatening (Burhan & van Leeuwen, 2016). Therefore, workplace discrimination may be stronger in a country that perceives Muslims and Arabs as threatening one's economy rather than one's physical security.…”
Section: Discussionmentioning
confidence: 99%